Development and utilization of primary winter synthetics to incorporate important new traits in winter wheat varieties. - CGIAR Research Program on Wheat (2018)
The synthetic germplasm has been developed, characterized, published and offered to CIMMYT cooperators through IWWIN (International Winter Wheat Improvement Network). The seeds have been deposited to CIMMYT Gene bank and shared with several breeding and research programs. The new varieties are now available through here: http://www.iwwip.org/Nursery